Biological control of Botrytis cinerea on strawberry fruit - KlechkovskіyY.; Mogilyuk, N.; Ignatyeva, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The article presents the results of testing a biological fungicide Serenade ASO, SC that protects strawberry against grey mould Botrytis cinerea Pers.